The value of CT in determining potential instability of simple wedge-compression fractures of the lumbar spine. - Campbell, S E; Phillips, C D; Dubovsky, E; Cail, W S; Omary, R A (American Journal of Neuroradiology, 1995)
PURPOSE To determine whether plain films alone are sufficient in the evaluation of stability of simple wedge-compression fractures of the lumbar spine. METHODS Plain films and CT scans of 53 consecutive patients seen during a 2-year period with lumbar spine fractures were retrospectively reviewed. Six readers blinded to the CT diagnosis independently read each patient's plain films. Plain-film findings were scored on a five-point graded response scale using criteria proposed by Gehweiler and Daffner. In addition, a fracture was considered to be possibly unstable if there was involvement of more than one vertebral level or greater than 50% loss of anterior vertebral body height. CT findings represented the standard for comparison. CT scans were independently evaluated by three additional readers. Two-column involvement, middle-column involvement alone but with retropulsion, multiple-level involvement, or greater than 50% loss of vertebral height indicated potential instability. RESULTS For 14 stable and 39 potentially unstable lumbar spine fractures, the pooled (mean) plain-film negative predictive value for detection of potentially unstable fractures was 0.62 (95% confidence interval, 0.53 to 0.70), with a sensitivity of 0.83 (95%, confidence interval; 0.78 to 0.87), and specificity of 0.80 (95% confidence interval, 0.70 to 0.87). CONCLUSION Plain films are not adequate for determining stability of lumbar spine fractures.